Phase II Study of Gemcitabine, Peg-Asparaginase, Dexamethasone and Methotrexate Regimen for Newly Diagnosed Extranodal Natural Killer/T-Cell Lymphoma, Nasal Type: Final Analysis With Long-Term Follow-Up and Rational Research for the Combination - Wang, Yu; Wang, Cai-Qin; Sun, Peng; Liu, Pan-Pan; Yang, Hang; Wang, Han-Yu; Rao, Hui-Lan; Li, Su; Jiang, Wen-Qi; Huang, Jia-Jia; Li, Zhi-Ming (Frontiers in Oncology, 2022)
Patients with extranodal natural killer/T-cell lymphoma (ENKTL), nasal type are benefit from peg-asparaginase, gemcitabine, and methotrexate. Therefore, we conducted a prospective phase II trial using a combination of these drugs as GAD-M regimen in naïve ENKTL patients, simultaneously, explored the combinational mechanism. The GAD-M regimen was administered for 6 cycles sandwiched by radiotherapy for stage I/II and 6 cycles for stage III/IV patients. After 6 cycles, the overall response rate of 36 patients was 91.6%, and the complete remission rate increased to 83.3%. The 3-year progression-free survival (PFS) and overall survival (OS) rates were 74.8% and 77.8%, respectively. The 5-year PFS and OS were 68.3% and 77.8%. No patient suffered from the central nervous system (CNS) relapse. Most patients experienced recoverable liver dysfunction and anemia in this study. The plasma MTX concentration ratio at 12 to 24 hr during the first cycle could be an early predictor of outcomes in ENKTL (PFS, P=0.005; OS, P=0.002). Additionally, we found that high dose MTX (HD-MTX) and gemcitabine had the synergistic effect of ENKTL cell in vitro. Mechanistically, we demonstrated that the combination could lead to obviously apoptosis in ENKTL cell with extremely release of reactive oxygen spices (ROS), which mediated by endoplasmic reticulum stress. In conclusion, the GAD-M regimen could be a new choice to newly diagnosed ENKTL, especially for stage I/II patients. Furthermore, our results showed the synergy effect of HD-MTX with gemcitabine in ENKTL. Clinical Trial Registration This trial was registered at www.clinicaltrials.gov as #NCT01991158.